THE IMMOBILIZATION OF LIPASE FROM MUCOR MIEHEI ON ZEOLITE MATRIX IN HYDROLYSIS OF PALM OIL PRODUCING FREE FATTY ACIDS WITH SOLVENT FREE SYSTEM (Jurnal Bahan Alam Terbarukan, 2018)
The enzymatic hydrolysis of palm oil can be conducted by using lipase produced from Mucor miehei to produce free fatty acid. This study aimed to compare the usage of lipase as free enzyme and as immobilized enzyme on zeolite matrix in the hydrolysis of palm oil as triglyceride producing free fatty acids which highly needed in various industrial sectors. Immobilization is an alternative hydrolysis reaction due to its usage on repetitive reaction, makes lipase reuseable, hence the whole process becomes efficient, and with moderate operational conditions. Solvent free reaction is applied, because the produced free fatty acids can be used directly in food, health, and natural flavorings industry. The palm oil used in the hydrolysis contains 0.815% initial free fatty acids as palmitate, in which water then added to it in weight ratio 1:3. Each effect of free lipase and immobilized lipase addition is 4%, 5%, 6%, 7%, 8%, and time reaction is 30, 60, 90, 120, 150 minutes are used as index to determine the amount of free fatty acids produced.Â  The results showed that Immobilized lipase has better ability than the free one in hydrolysis of triglyceride in palm oil producing free fatty acid with 8% lipase addition and time reaction of 120 minutes. Palm oil hydrolysis using free lipase produced the highest FFA of 1.9747% after the addition of 5% lipase concentrate, with time reaction of 60 minutes. Meanwhile, palm oil hydrolysis using immobilized lipase produced the highest FFA of 1.9747% after the addition of 8% lipase concentrate, with time reaction of 120 minutes.